Pemberdayaan Desa Kedu Baru Melalui Pengolahan Tanaman Toga Menjadi Produk Ekonomi Kreatif Bernilai Tambah - Ayu Lestari (Jurnal INDONESIA RAYA (Pengabdian pada Masyarakat Bidang Sosial, Humaniora, Kesehatan, Ekonomi dan Umum), 2025)
Community service is one of the implementations of the university’s tridharma, aimed at providing real benefits for society. Kedu Baru Village has natural resources in the form of medicinal plants (toga), which have so far been mostly used traditionally and have not been optimally managed. Based on this condition, this community service program focused on empowering the community through education and hands-on practice in processing medicinal plants into value-added creative economy products.The implementation methods included socialization, training, and mentoring for local community groups. Participants were provided with knowledge of the benefits of medicinal plants, hygienic processing techniques, and basic marketing strategies. The processed products included herbal drinks, instant herbal powders, and essential oils, which are expected to increase the economic value and competitiveness of the community.The results showed an increase in community knowledge and skills in processing toga plants, as well as the growth of entrepreneurial spirit among participants. In addition, the processed toga products offered an alternative source of income to support family economies. Thus, this activity not only contributed to improving community health through the utilization of medicinal plants but also encouraged the creation of a sustainable creative economy in Kedu Baru Village. Bottom of Form